Modelling of Soil Erosion Susceptibility Using the Multi-Influencing Factor Method in the Amizmiz Basin, Morocco - Saloua Agli; Algouti Ahmed; Algouti Abdellah; Farah Abdelouahed; Moujane Said; Abdelfattah Aboulfaraj; El ghouat Akram (Forum Geografi, 2024)
In the Western High Atlas of Morocco, soil loss caused by hydraulic erosion is a serious environmental issue that has led to the destruction of arable land and the feeding of surface water with large solid loads, resulting in major flood damage and the silting of dams. This study aims to identify areas vulnerable to hydraulic erosion in the Amizmiz watershed in the Western High Atlas to facilitate effective management of natural resources. The methodology adopted in this study is based on the multi-influencing factor (MIF) method coupled with remote sensing and geographic information system (GIS) data. The resulting erodibility map shows that areas with low to very low erosion potential represent 13% and 6% of the watershed, respectively, occupying the downstream and eastern parts of the basin, whereas 62% of the basin is classified as medium-risk. The remaining 19% of the watershed comprises high-risk areas, which are generally located in the axial and western zones. The validation value (AUC) obtained from the ROC curve is 0.78, confirming the sufficient predictive capacity of the MIF model for identifying areas vulnerable to hydraulic erosion in the Amimiz watershed.